2021
DOI: 10.1038/s41378-021-00304-8
|View full text |Cite
|
Sign up to set email alerts
|

Propagating acoustic waves on a culture substrate regulate the directional collective cell migration

Abstract: Collective cell migration plays a critical role in physiological and pathological processes such as development, wound healing, and metastasis. Numerous studies have demonstrated how various types of chemical, mechanical, and electrical cues dictate the collective migratory behaviors of cells. Although an acoustic cue can be advantageous because of its noninvasiveness and biocompatibility, cell migration in response to acoustic stimulation remains poorly understood. In this study, we developed a device that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…[ 31 ] Furthermore, cell migration‐related actin bundles are affected by propagating acoustic waves on culture substrates. [ 32 ] These studies supports our results, but details of actin dynamics of cells in the levitated droplet have not been further investigated.…”
Section: Discussionsupporting
confidence: 79%
“…[ 31 ] Furthermore, cell migration‐related actin bundles are affected by propagating acoustic waves on culture substrates. [ 32 ] These studies supports our results, but details of actin dynamics of cells in the levitated droplet have not been further investigated.…”
Section: Discussionsupporting
confidence: 79%
“…Further, the proliferation rate and glucose consumption of the cells, which are measures of biocompatibility, were not affected by the culture on LN as shown in Fig. 3 C. In any case, two separate studies have each indicated that mechanical stimulation of cells cultured on either LN or glass produce similar effects on the cells regardless of the culture surface [52] , [53] . We conclude this method of evaluating the cell adhesion on the ultrasound transducer should be meaningful for cells bound onto glass substrates.…”
Section: Discussionmentioning
confidence: 81%
“…Further, the results were supported by past publications, helping to validate our approach. In future work, the core idea of the developed system in employing high-frequency-ultrasound-induced acoustic streaming may be applied to different culture surfaces or even to the in/ex vivo environment, since we have already developed the technology to propagate ultrasound from the transducers to other materials [53] , [61] . Cell adhesion can be evaluated in other conditions: other cell species, surface modifications engineered with mechanical or biochemical technologies, or culture environments with various chemical species or mechanical stimulation, all based on the idea of using acoustic streaming.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular elongation, angular orientation, and collagen deposition characteristics observed after maturation of these constructs (Figure 5) are comparable to the literature on the effects of topographical cues provided by aligned fibers/patterns created via electrospinning, [ 10 ] support‐assisted bioprinting, [ 50 ] and soft lithography. [ 51 ] In future, building upon the findings of this study and recent SAW‐based literature about influences of acoustic stimulation beyond patterning, [ 52,53 ] we will investigate the effects of periodic BAW stimulation of UAB‐patterned hybrid constructs during dynamic culture (i.e., in a perfusion bioreactor) on cell proliferation, directional migration, and ECM production, with the goal to further enhance the bulk anisotropy and biofunctionality of the constructs.…”
Section: Uab Of Constructs Featuring Anisotropic Cartilage Tissuementioning
confidence: 99%